Multiple-agent promotion in a grocery store: effects of modality and variability of agents on customer memory - Takato Mizuho; Takato Mizuho; Yuki Okafuji; Yuki Okafuji; Jun Baba; Jun Baba; Takuji Narumi (Frontiers in Robotics and AI)
The use of social robots for product advertising is becoming prevalent. Previous studies have demonstrated that social robots can positively impact ad hoc sales recommendations. However, the essential question of “how effectively customers remember the advertised content” remains unexplored. To address this gap, we conducted a field study where physical robots or virtual agents were stationed at two locations within a grocery store for product promotion. Based on prior research, we hypothesized that customers would exhibit better recall of promotional content when it is heard from different agents rather than the same agent. Moreover, we posited that customers would exhibit more favorable social attitudes toward physical robots than virtual agents, resulting in enhanced recall. The results did not support our hypotheses, as no significant differences were observed between the conditions. However, when the physical robot was used, we observed a significant positive correlation between subjective ratings such as social presence and recall performance. This trend was not evident when the virtual agent was used. This study is a stepping stone for future research evaluating agent-based product promotion in terms of customer memory.